Promoting Regional Cinema In India To Preserve Cultural Heritage - A Critical Analysis On Language Revitalization Efforts - Ms. Rimma Quadros, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Cinema is relatable to people’s lives in India or it wouldn’t be wrong to say that cinema is an emotion to them. The 70mm screen gives an escape from the hustles and bustles of daily life and stress. Cinema gives liberty to cry, sing, laugh, and dance along. Films are made in every corner in India. Around 1800 films are made every year constantly in different languages and some are critically acclaimed across the nation and the world. Indian cinema makes world’s biggest film industry with over 3.5 billion tickets sold in 2011 all over the world. Indian films have wide exposure across Southeast Asia and realistic films reach all over the world, including Eastern Africa, North America, the Middle East, Europe, and Asia. Considering the number of films produced and people working in the film industry, Bollywood is considered one of the biggest film industries in the world. This study aims to discuss various regional film industries in India representing various Indian languages and recent efforts on language revitalization through regional films.